Revitalisasi identitas nasional di kalangan generasi milenial: strategi pendidikan dan kultural - anwar, muhammad zidan (Maliki Interdisciplinary Journal, 2025)
As the most prominent demographic group in Indonesia, millennials encounter considerable challenges in preserving their national identity in an era shaped by globalization and digital influence. This article explores the degree to which national identity continues to influence millennials’ perspectives and actions, while also examining strategies to strengthen it through character-building education and the reinforcement of cultural values. The study underscores the importance of adapting national identity to contemporary contexts and reimagining how national values are conveyed, ensuring their relevance to millennial lifestyles.